Root absorption and effects of ZnO nanoparticles on Phaseolus vulgaris plants - Cruz, Tatiana Nishida Máximo da (2018)
Nanotechnology has been used in many fields. Nanoparticles are already found as a component of many products. However, the use of nanoparticles in agriculture is still a matter of concern because of its interaction with biological tissues. Aiming to evaluate NPs effects on Phaseolus vulgaris plants, this study investigated: how ZnO NPs dispersions are absorbed by plant roots; how it is translocated and accumulated in plant tissues; physiological and morphological effects, and compare results with ZnSO4 solution. In vivo X-ray fluorescence spectroscopy revealed that source, NP size, concentration and coating with surfactants affect Zn release and uptake. Regardless the source, at high doses, there is a gradient of Zn concentration from root to shoot. In vivo X-ray absorption spectroscopy showed that Zn is taken up bound mainly to citrate and malate. Entire NPs were observed only in plants whose roots were injured. X-ray fluorescence microanalysis revealed that root to shoot Zn transport can occurs through xylem and cortex, and both sources presented the same Zn distribution inside the stems. Infrared gas analysis showed a decrease in the water conductance, photosynthetic and transpiration rate after 48 hours of exposure to ZnO and ZnSO4 comparing with the control. Root length, shoot height, root dry mass, shoot fresh mass and leaf area were more impaired by Zn concentration than sources